2012
DOI: 10.1186/1471-230x-12-106
|View full text |Cite
|
Sign up to set email alerts
|

Goat milk with and without increased concentrations of lysozyme improves repair of intestinal cell damage induced by enteroaggregative Escherichia coli

Abstract: BackgroundEnteroaggregative Escherichia coli (EAEC) causes diarrhea, malnutrition and poor growth in children. Human breast milk decreases disease-causing bacteria by supplying nutrients and antimicrobial factors such as lysozyme. Goat milk with and without human lysozyme (HLZ) may improve the repair of intestinal barrier function damage induced by EAEC. This work investigates the effect of the milks on intestinal barrier function repair, bacterial adherence in Caco-2 and HEp-2 cells, intestinal cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…Although some studies reported a decrease in migration of stomach cells infected with EPEC ( 20 , 21 ), mechanisms were not investigated. Our group described that infection by enteroaggregative E. coli (EAEC) decreased the number of migrating intestinal cells ( 22 ), whereas, in the present results, we determined that EPEC strains significantly reduced the number of migrating cells and that bacterial strains differentially inhibited migration. The most considerable reduction in cell migration was due to infection with EPEC strain E2348/69, compared to EPEC LDI001 and E. coli HS strains.…”
Section: Discussioncontrasting
confidence: 54%
“…Although some studies reported a decrease in migration of stomach cells infected with EPEC ( 20 , 21 ), mechanisms were not investigated. Our group described that infection by enteroaggregative E. coli (EAEC) decreased the number of migrating intestinal cells ( 22 ), whereas, in the present results, we determined that EPEC strains significantly reduced the number of migrating cells and that bacterial strains differentially inhibited migration. The most considerable reduction in cell migration was due to infection with EPEC strain E2348/69, compared to EPEC LDI001 and E. coli HS strains.…”
Section: Discussioncontrasting
confidence: 54%
“…In an in vitro model, intestinal epithelial cell migration was significantly decreased in the presence of enteroaggregative E. coli (EAEC) alone but was restored in the presence of milk (Carvalho et al 2012). Milk from hLZ transgenic goats improved migration significantly more than control milk.…”
Section: Effects Of Lysozyme Milkmentioning
confidence: 98%
“…Both milks significantly reduced EAEC adhesion to Caco-2 cells and transgenic milk resulted in less colonization than control milk using a HEp-2 cell line assay. While normal goat milk is able to repair intestinal barrier function damage induced by EAEC the hLZ transgenic goat milk provides further protection (Carvalho et al 2012). In an in vivo model of diarrhea using young pigs infected with enterotoxigenic E. coli (ETEC), pigs consuming hLZ-milk recovered from clinical signs of infection faster than pigs consuming control milk, with significantly improved fecal consistency and activity level (Cooper et al 2013).…”
Section: Effects Of Lysozyme Milkmentioning
confidence: 99%
“…The minor constituents of goat milk, namely lysozyme and transforming growth factor-β (TGF-β), seem to offer additional protection against intestinal cell damage/inflammation [147]. Several authors have shown that oral administration of TGF-β has anti-inflammatory effects at the intestinal level in animal models of colitis [148].…”
Section: Immunomodulatory/anti-inflammatory Peptidesmentioning
confidence: 99%